METHODS FOR ANALYZING THE EFFECTIVENESS OF THE LOGISTICS OF ENSURING AVIATION GROUND EQUIPMENT - Тамаргазін, О.А.; Ліннік, І.І.; Олег, М.В.; Крамаренко, Т.Ю. (Science-based technologies, 2014)
The methods of determination of efficiency of the system of logistical support of aviation ground equipment that is used for providing of airplanes flights during liquidation of technogenic or natural emergencies are investigated in the article. For this task determination logical-pobability method that contains three stages is used: logical function of capacity recording, transformation of logical function to the form of complete substitution and complete substitution of all logical variables by probabilities and logical operations by arithmetic operations. With the aim of simplification of realization of analysis it offered to these stages to add another intermediate stage - partial substitution of logical variables by probabilities. Therefore instead of form of complete substitution a logical function transforms to the form of transition with partial substitution, and as a result of partial substitution the so-called mixed form of function of probability is built, that contains and probabilities, and logical variables, arithmetic and logical operations simultaneously.